2021
DOI: 10.28991/cej-2021-03091640
|View full text |Cite
|
Sign up to set email alerts
|

Coal ash Portland Cement Mortars Sulphate Resistance

Abstract: Coal fly ash (CFA), coal bottom ash (CBA) are residues produced in thermo-electrical power stations as result of the coal combustion in the same boiler. Therefore, some characteristics of the coal fly ash (CFA) are comparable with those of the coal bottom ash (CBA). Nevertheless, coal bottom ash size is larger than coal fly ash one. Consequently, it was found that it is necessary to grind the coal bottom ash (CBA) to reach a similar size to that one of the CFA. The objective of this paper is to evaluate the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[9] Argiz and Menéndez introduced CBA as a gel material into cement and found that the concrete's resistance to chloride and sulfate corrosion improved with an increase in the CBA content (within the range of 25%). [10,11] Özkılıç et al [12] introduced varying proportions of waste glass aggregate (WGA) into a fixed ratio of alkali-activated fly ash-based geopolymer concrete. They conducted tests on its physical properties and observed that the concrete's performance was inversely related to the proportion of WGA but directly proportional to the NaOH concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Argiz and Menéndez introduced CBA as a gel material into cement and found that the concrete's resistance to chloride and sulfate corrosion improved with an increase in the CBA content (within the range of 25%). [10,11] Özkılıç et al [12] introduced varying proportions of waste glass aggregate (WGA) into a fixed ratio of alkali-activated fly ash-based geopolymer concrete. They conducted tests on its physical properties and observed that the concrete's performance was inversely related to the proportion of WGA but directly proportional to the NaOH concentration.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Argiz and Menéndez introduced CBA as a gel material into cement and found that the concrete's resistance to chloride and sulfate corrosion improved with an increase in the CBA content (within the range of 25%). [ 10 , 11 ] Özkılıç et al. [ 12 ] introduced varying proportions of waste glass aggregate (WGA) into a fixed ratio of alkali‐activated fly ash‐based geopolymer concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in compressive strength is due to its hydration process, which allows it to harden and become compact as the concrete ages. When the amount of bottom ash used increases, the compressive strength of concrete decreases both at early and 28-day ages [3]. In earlier research, the ANN model was developed to predict the compressive strength of concrete.…”
Section: Introductionmentioning
confidence: 99%